Proposed Model for Asset Lifecycle Management through the Internet of Things - Daneshpour , Ali; Banitalebi Dehkordi , Bahareh; Jafari Dehkordi , Hamidreza (Business, Marketing, and Finance Open, 2025)
Given the profound and extensive developments in information technology across the business landscape, the domain of asset and resource management within large-scale manufacturing corporations is also expected to undergo significant transformation. As asset management is one of the core and enduring managerial functions in large organizations, and as top executives consistently seek up-to-date, innovative, and technology-driven solutions for optimal resource management, this study aims to propose a model for asset lifecycle management through the Internet of Things (IoT). The research, in terms of its aim, is applied-developmental in nature, and methodologically, it is a non-experimental (descriptive) study conducted using a cross-sectional survey approach. Regarding the research method, it should be noted that a qualitative content analysis was first conducted to design an IoT-based asset lifecycle management model by reviewing 60 reputable Persian and English scientific articles published between 2011 and 2023. Additionally, using the grounded theory method, in-depth interviews were conducted with 10 experts and managers in the fields of IoT and asset management. After open coding of the interview transcripts and generating frequency charts for each interview's codes, axial coding was performed to identify major categories. As a result, 7 core themes and 38 sub-themes were extracted and organized into the proposed model for implementing IoT-based asset lifecycle management. The findings revealed that by analyzing and categorizing the descriptive codes extracted from the interview transcripts, a total of 38 sub-themes were identified. These were grouped into 7 main themes based on their semantic proximity and relevance: asset lifecycle management, asset lifecycle planning, asset acquisition, strategic alignment, IoT-enabled reporting, process automation through IoT, and IoT implementation within the organization. The outcomes of the proposed model demonstrate the influential role of the Internet of Things as an emerging technology in asset management. Its practical application can lead to a major transformation in safeguarding and optimizing the management of institutional assets and properties.